Highly sensitive and selective miRNA detection based on a closed ring probe and multiple signal amplification. Issue 96 (14th November 2016) - Tang, Yaqin; He, Xiao; Zhou, Zhenxia; Tang, Jiakun; Guo, Rong; Feng, Xuli
Abstract : A highly sensitive and selective miRNA detection approach based on a small circular probe and dual signal amplification has been reported. Abstract : A highly sensitive and selective miRNA detection approach based on a small circular probe and dual signal amplification has been reported. We successfully applied the assay for quantitative let-7a detection in cell lysates and the results agreed well with those of qRT-PCR.